Falsified Medicines, a Crime without Punishment - Gentilini, Marc; Duteil, Quentin (Integrative Journal of Medical Sciences, 2017)
Falsified medicines are a global threat that does not stop growing. Its trafficking causes more deaths than malaria while being more profitable than drug smuggling. Not only it threatens public health but also the economic development of the poorest countries. Taking advantage of globalization, it affects now every country even the most developed, and any type of pharmaceutical products, ranging from treatments against cancer to erectile dysfunction pills. Considered the biggest black market in the world, it remains underestimated by politicians, health professionals, and the public. Raising awareness at every level about the health risks associated with falsified medicines is a vital emergency.